زكاة عروض التجارة دراسة فقهية مقارنة - بوخلوة, المهدي; حمادو, عباس; شلغوم, محمد الطاهر (University of Eloued-جامعة الوادي, 2014)
إن للزكاة مكانة عظيمة في الإسلام؛ فهي الركن الثالث بعد الشهادتين والصلاة، وقد عني بمباحثها العلماء قديماً وحديثاً، ولا يزال البحث يتجدد في هذه الشعيرة؛ لعناية الشارع بها، ولأنها تتعلق بالجانب المالي في حياة الناس. وقد تناول هذا البحث زكاة موارد مالية حديثة، هي زكاة عروض التجارة ، والتي ظهرت بأثواب جديدة في هذا العصر كمصادر كسب لها مكانتها في حياة الناس اليومية؛ فبينت الدراسة الآراء الفقهية الواردة في حكم زكاتها، مع الأدلة، والمناقشة، والترجيح. وخلص البحث إلى ترجيح القول بوجوب زكاتها، لقوة دليلهم ولأنه الأنفع للمستحق غالبا مع توضيح كيفية زكاتها، والمقدار الواجب فيها . Executive Summary: That great place in Islam Zakat is the third pillar after the shahaadatayn, prayer, and on its fields of old & new scholars, research continues in this ritual is renewed, for the attention of the street, and it concerns the financial aspect of people's lives. This research has addressed the zakaah on modern financial resources, is zakaah on goods of trade, which appeared in new dresses in this era as a source of earning her place in the daily lives of people, the study showed jurisprudence contained in ruling on zakaah on that, with evidence, discussion, and weighting. The research concluded that the likelihood of saying that zakaah on their force, and it is often useful to due with how zakaah on, the amount of duty which
مذكرة ليسانس
Keywords: /دراسة فقهية/زكاة /عروض التجارة; /Étude jurisprudentielle/Zakat/Offres commerciales